Nuclear and organellar phylogenies provide insights into evolutionary history and species boundaries in Galdieria - Manuela Iovinella; Sarah C.L. Lock; Luke C.M. Mackinder; James P.J. Chong; Georg A. Feichtinger; Sally James; Daniel Jeffares; Antonino Pollio; Emanuele Del Guacchio; Hwan Su Yoon; Claudia Ciniglia; Seth J. Davis (Algal Research, 2026)

Expression of biomineralization‐related ion transport genes in Emiliania huxleyi - Luke Mackinder; Glen Wheeler; Declan Schroeder; Peter von Dassow; Ulf Riebesell; Colin Brownlee (Environmental Microbiology, 2011)
Summary Biomineralization in the marine phytoplankton Emiliania huxleyi is a stringently controlled intracellular process. The molecular basis of coccolith production is still relatively unknown although its importance in global biogeochemical cycles and varying sensitivity to increased pCO 2 levels has been well documented. This study looks into the role of several candidate Ca 2+ , H + and inorganic carbon transport genes in E. huxleyi , using quantitative reverse transcriptase PCR. Differential gene expression analysis was investigated in two isogenic pairs of calcifying and non‐calcifying strains of E. huxleyi and cultures grown at various Ca 2+ concentrations to alter calcite production. We show that calcification correlated to the consistent upregulation of a putative HCO 3 ‐ transporter belonging to the solute carrier 4 (SLC4) family, a Ca 2+ /H + exchanger belonging to the CAX family of exchangers and a vacuolar H + ‐ATPase. We also show that the coccolith‐associated protein, GPA is downregulated in calcifying cells. The data provide strong evidence that these genes play key roles in E. huxleyi biomineralization. Based on the gene expression data and the current literature a working model for biomineralization‐related ion transport in coccolithophores is presented.